Unexpected Facets of Images of Officials by N. V. Gogol and V. F. Odoevsky - Yu. N. Sytina (Научный диалог)
The issues on the multifaceted images of officials in the Russian literature of the 1830- 1840s are considered. The results of a comparative analysis of the works of N. V. Gogol and V. F. Odoevsky are presented. Particular attention is paid to Poprishchin from the “Diary of a Madman” and the order Sevastyanich from “The Tale of a Dead Body Who Belongs to No One”. The author draws attention to the fact that the heroes go beyond the behavioral model, as if attributed to them by their social role. It is shown that poetry does not disappear from their existence; officials are capable of creativity and creation of their own works. The irreducibility of the images of officials is proved only to illustrate social reality, the striving for their individualization, drawing a rich inner world is emphasized. The novelty of the research is seen in the fact that unexpected facets of the images of officials in Gogol and Odoevsky are revealed in their relationship. The commonality of the writers’ worldviews and the similarity of their poetics are shown, which is manifested, in particular, in the fact that science fiction occupies an important place in the artistic world of works about officials.